Pengaruh Profitabilitas Terhadap Harga Saham Pada Jakarta Islamic Index Tahun 2018-2020 - Fitriani, Melsa; Indra, Yetti Afrida (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2022)
This study aims to determine the effect of Return On Assets, Return On Equity, and Net Profit Margin on stock prices on the Jakarta Islamic Index in 2018-2020. The data used in this study is secondary data with documentary and library data collection techniques sourced from www.idx.co.id. The population of this study is all issuers included in the Jakarta Islamic Index on the Indonesia Stock Exchange with a period of 3 years, namely between 2018-2020, totaling 30 companies. The data analysis technique used in this study is panel data regression with Eviews 8 software for the Fixed Effect Model estimation model, where this model is tested with the Chow test and Hausman test. The results of this study indicate that Return On Assets and Return On Equity have a positive and significant effect on stock prices while Net Profit Margin has a positive and insignificant effect on stock prices in JII in 2018-2020. R-squared value of 0.867787 indicates that stock prices can be influenced by the value of Return On Assets, Return On Equity, and Net Profit Margin of 86.78%, while the remaining 13.22% is influenced by values or other factors outside these variables.